Health Literacy Level and its Related Factors among the Elderlies in Ilam in 2015 - M Borji; A Tarjoman; M Otaghi; E Salimi; A Naseri (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: People with low health literacy have less knowledge about their health status, receive fewer preventive services, and their chronic diseases are less controlled. This study aimed to investigate the relationship between health literacy and physical health status of the elderlies in Ilam in 2015. Materials & Methods: In this descriptive study, 250 elderlies were selected by two-stage cluster sampling in Ilam. The tools were Adult Health Literacy Questionnaire, Activities of Daily Living (ADL), And questions about the physical performance of the SF-36 Quality of Life Questionnaire. Validity and reliability of these tools have been confirmed in previous studies. Data were analyzed by SPSS version 16, statistical t-test (for variables in the two groups) and ANOVA (for variables more than the two groups). Results: The results showed that 50.4% of the elderlies had inadequate health literacy. There were significant relationships between health literacy and age, sex, occupation, education, residence, previous chronic disease and readmission (P < 0.05); however, there was no significant relationship between health literacy and income. The elderlies who were independent or had any limitations in physical activity had higher health literacy (P= 0.001). Conclusion: Regarding the low level of health literacy of older people in Ilam, it is necessary to implement interventions to enhance their health literacy for improving their physical health status and, consequently, the quality of their lives.